Frequency of PPD (Para-Phenylenediamine) Allergy in Hair Dye Users in Faisalabad - Shakeel Ahmed, Mehwish Khan Abdali, Filza Hafeez, Haafiza Hina Imtiaz, Rabia Ashfaq, Aisha Malik (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the frequency of PPD allergic contact dermatitis in hair dye users in Faisalabad district. Study Design: Cross Sectional study. Place and Duration of Study: Dermatology Outpatient Department of District Headquarter Hospital, Faisalabad from 01-07-2018 to 31-12-2018. Methodology: A cross sectional study was carried out in Dermatology Outpatient Department and 135 patients were included. Male and female patients were included in this study with the age between Results: A total number of 135 patients were included in this study. Gendser distribution showed that there were 110 (81.5%) males and 25 (18.5%) females. The mean age of the patients was 38.04±4.96 years. The mean duration of hair dye use of the patients was 4±1.5 years. There were 92 (68.1%) patients between 30-40 years of age and 43 (31.9%) patients between 41-50 years of age. There were 80 (59.3%) patients between 3-4 years of duration of hair dye and 55 (40.7%) patients between 4-5 years of duration of hair dye. PPD allergic dermatitis was observed in 13 (9.6) patients. There was no association between gender (p=0.232), age (p=0.591) and duration of hair dye use (p=0.676) with respect to PPD allergic dermatitis. Conclusion: Para-phenylenediamineis the commonest cause of hair dye contact dermatitis. Patients can present with a variety of clinical manifestations, including severe reactions. Patch testing remains the gold standard method for confirming PPD allergy. Avoiding future contact with permanent and semi-permanent hair dyes is the standard preventative measure. Keywords: Allergy, Hair, Phenylenediamine, Para-Phenylenediamine